Abatacept in the treatment of polyarticular JIA: development, clinical utility, and place in therapy - Ofra Goldzweig; Philip J Hashkes (Dove Medical Press, 2011)
Ofra Goldzweig1, Philip J Hashkes2,31Rainbow Babies and Children's Hospital, Cleveland, OH, USA; 2Pediatric Rheumatology Unit, Shaare Zedek Medical Center, Jerusalem, Israel; 3Cleveland Clinic Lerner Medical School of Case Western Reserve University, Cleveland, OH, USAAbstract: Juvenile idiopathic arthritis (JIA) is a group of chronic arthritides affecting children. The polyarthritis category, affecting five or more joints in the first six months, tends to be more aggressive, leading to a destructive joint disease with significant morbidity, disability, and costs to society. The current treatment regimen, which primarily combines methotrexate and tumor necrosis factor alpha (TNF-α) blockade, still leaves a significant group of patients with an inadequate response. Therefore, the development of new medications that act via other mechanisms of pathogenesis is necessary. T cell lymphocytes are key components in the immune reaction in JIA. Cytotoxic lymphocyte-associated antigen-4 (CTLA-4) is a potent inhibitor of the costimulation pathway necessary to activate T cells. Abatacept is a recombinant fusion protein comprising the extracellular part of human CTLA-4 connected to a modified Fc part of IgG-1. In a randomized, multinational, blinded withdrawal study in children with polyarticular JIA, abatacept was found to be effective in about 70% of the patients, including 39% of TNF-α blockade failures, with significantly fewer flares occurring during the withdrawal phase than in patients receiving placebo. Abatacept continued to show good efficacy in a three-year open-label extension study, with a beneficial effect on health-related quality of life. The safety profile of abatacept is generally good. In 2008, the US Food and Drug Administration approved abatacept for use in children over six years of age with JIA and a polyarticular course. In 2010, the European Medicines Agency gave approval for abatacept to be used in combination with methotrexate for those who fail at least one disease-modifying medication and TNF-α blockade.Keywords: juvenile idiopathic arthritis, treatment, abatacept